Health, social participation, and rights - Delgado Campos, Victoria Ixshel (Horizonte Sanitario, 2025)
Abstract Mexico is experiencing a period of political, economic, cultural, and social transformation. The public health sector is no stranger to these changes, among which stands out a vision that places people at the center of government actions, not as passive subjects and recipients of benefits, but as subjects who demand the fulfillment of their rights. This is undoubtedly one of the hallmarks of the current administration, which seeks the active participation of the population. This paradigm shift compels us to continue the debate around two central ideas: 1) the social component of health; and 2) the challenges of health policies from a rights-based perspective. Regarding this, the proposal on the approach of Social Medicine and Collective Health is presented, and then some challenges observed in implementing rights-based health policies are discussed. Among the main challenges are: overcoming the fragmentation of the health system, defining collective health indicators, generating health policies with feasible solutions but within social health frameworks, and making theoretical elements such as the social determination of health operational. What we see in the country today is an invitation to reflect on the potential for people's participation when they are seen as key players in government action.KeywordsMexico, right to health, social participation.